2003
DOI: 10.2337/diabetes.52.3.675
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal and Postprandial Free Fatty Acid Kinetics in Normal and Type 2 Diabetic Subjects

Abstract: Whether free fatty acid (FFA) rate of appearance (R a ) is increased in type 2 diabetes is controversial. To characterize nocturnal and postprandial abnormalities in FFA kinetics and to determine the effects of treatment with insulin sensitizers on lipolysis, we measured palmitate R a in control subjects (n ‫؍‬ 6) and individuals with poorly controlled, sulfonylurea-treated type 2 diabetes (HbA 1c ‫؍‬ 8.7 ؎ 0.2%, n ‫؍‬ 20), the latter before and at the end of 12 weeks of treatment with troglitazone (600 mg/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 49 publications
5
89
3
Order By: Relevance
“…Accordingly, in the present study a tendency was observed for a less significant suppression of arterial palmitate concentration and systemic palmitate turnover rate in diabetic patients during the hyperinsulinaemic-euglycaemic clamp. This observation is also in agreement with the impaired postprandial suppression of systemic fatty acid turnover demonstrated in type 2 diabetic patients [26]. From the present study it is clear that the skeletal muscles of the leg more than those of the arm may play an important role in the reduced insulin sensitivity with regard to the systemic fatty acid turnover in type 2 diabetes, since no suppression was observed in palmitate uptake or release by the leg.…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, in the present study a tendency was observed for a less significant suppression of arterial palmitate concentration and systemic palmitate turnover rate in diabetic patients during the hyperinsulinaemic-euglycaemic clamp. This observation is also in agreement with the impaired postprandial suppression of systemic fatty acid turnover demonstrated in type 2 diabetic patients [26]. From the present study it is clear that the skeletal muscles of the leg more than those of the arm may play an important role in the reduced insulin sensitivity with regard to the systemic fatty acid turnover in type 2 diabetes, since no suppression was observed in palmitate uptake or release by the leg.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies suggested that thiazolidinediones lower NEFA concentrations in type 2 diabetes via improved insulin suppression of lipolysis [17][18][19][20]. In the current study of non-diabetic adults with upper body obesity we did not find greater insulin suppression of lipolysis.…”
Section: Discussioncontrasting
confidence: 36%
“…Examples include diet/exercise and thiazolidinediones [16]. Thiazolidinediones, peroxisome proliferator-activated receptor-γ agonists, have been reported to enhance the insulin suppression of lipolysis in type 2 diabetes [17][18][19][20]; this could account for the improved insulin regulation of glucose disposal seen in response to thiazolidinediones.…”
Section: Introductionmentioning
confidence: 99%
“…The biguanide metformin decreases the high hepatic glucose output observed in type 2 diabetes, whereas thiazolidinediones such as pioglitazone or rosiglitazone increase muscle glucose uptake in response to insulin and are called insulin sensitisers. Metformin and thiazolidinediones have been reported to decrease the plasma concentrations of non-esterified fatty acids in type 2 diabetic patients [17][18][19][20][21] and the lipolytic rate in obese humans [22][23][24]. In rodent adipocytes, biguanides and thiazolidinediones are able to activate AMPK, and biguanides are able to reduce lipolysis [8,25,26].…”
Section: Introductionmentioning
confidence: 99%